2023
DOI: 10.1021/acs.inorgchem.2c03624
|View full text |Cite
|
Sign up to set email alerts
|

The Adjustability of Physicochemical Properties: Comparison of 1-Vinyl-5H-tetrazole and 1-Allyl-5H-tetrazole as Ligands in 3d Metal Energetic Coordination Compounds

Abstract: Energetic coordination compounds (ECCs) show promising properties to be used as potential substitutes for highly toxic lead-containing primary explosives. The concept is to combine the three building blocks: (i) ligand, (ii) transition metal, and (iii) anion, acting as (i) fuel, (ii) matrix, and (iii) oxidizer (e.g., ClO4 –, NO3 –, ClO3 –) or energetic component (e.g., DN–, N3 –, picrate, styphnate, trinitrophloroglucinate). By variation of the ligands, the complexes’ properties can be adjusted toward their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…6−10 Klapoẗke has made outstanding contributions in this field. Specifically, they used tetrazole derivatives as ligands to prepare a series of ECCs, such as [Cu(1-VTZ) 6 ](ClO 4 ) 2 , 11 [Cu(1-NMT) 6 ](ClO 4 ) 2 , 12 and [Cu(1-NET) 6 ](ClO 4 ) 2 13 (1-VTZ: 1-vinyl-5H-tetrazole, 1-NMT: 1N-(nitromethyl)-5H-tetrazole, 1-NET: 1-nitratoethyl-5H-tetrazole). Not surprisingly, these ECCs have the potential to be used as primary explosives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6−10 Klapoẗke has made outstanding contributions in this field. Specifically, they used tetrazole derivatives as ligands to prepare a series of ECCs, such as [Cu(1-VTZ) 6 ](ClO 4 ) 2 , 11 [Cu(1-NMT) 6 ](ClO 4 ) 2 , 12 and [Cu(1-NET) 6 ](ClO 4 ) 2 13 (1-VTZ: 1-vinyl-5H-tetrazole, 1-NMT: 1N-(nitromethyl)-5H-tetrazole, 1-NET: 1-nitratoethyl-5H-tetrazole). Not surprisingly, these ECCs have the potential to be used as primary explosives.…”
Section: Introductionmentioning
confidence: 99%
“…In nitrogen-rich materials, energetic coordination compounds (ECCs) with unique coordination structures have attracted the attention of scientists due to their simple preparation, high product purity, and excellent explosive performance. Klapötke has made outstanding contributions in this field. Specifically, they used tetrazole derivatives as ligands to prepare a series of ECCs, such as [Cu­(1-VTZ) 6 ]­(ClO 4 ) 2 , [Cu­(1-NMT) 6 ]­(ClO 4 ) 2 , and [Cu­(1-NET) 6 ]­(ClO 4 ) 2 (1-VTZ: 1-vinyl-5 H -tetrazole, 1-NMT: 1N-(nitromethyl)-5 H -tetrazole, 1-NET: 1-nitratoethyl-5 H -tetrazole). Not surprisingly, these ECCs have the potential to be used as primary explosives.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research, multidisciplinary development, and new requirements, more and more new materials have been used in primary explosives. , Among them, energetic coordination compounds (ECCs) have entered the perspective of researchers due to their unique structure and performance advantages . Because of its simple preparation, good performance, easy amplification, and high purity, it is favored by researchers, and Klapötke has made outstanding contributions in this regard. …”
Section: Introductionmentioning
confidence: 99%
“…In the field of ECCs, Klapötke have made significant contributions, with their research focusing on ECCs using tetrazole derivatives as ligands. [11][12][13] However, since the [N] in the tetrazole ring is connected, it contains a lot of chemical potential energy, and the derived groups are often high-energy explosive groups, such as 1-(nitromethyl)-5H-tetrazole, 14 1-(azidomethyl)-5H-tetrazole, 15 and 1-vinyl-5H-tetrazole, 16 meaning that the ligand itself shows relatively high explosive performance. Therefore, although these [ClO 4 − ]-based complexes have high energy, they are very sensitive to mechanical stimuli, and we have found that complexes prepared using stereoisomers have different structures and properties.…”
Section: Introductionmentioning
confidence: 99%